An Internet of Things (IoT)-Based Room Temperature and Humidity Monitoring System Using ESP8266 and DHT22 Sensors - Syelviana Meisyaroh; Hari Purwadi; Ansar Rizal (Journal of Engineering, Electrical and Informatics, 2026)
Monitoring room temperature and humidity is an important aspect to maintain comfort and environmental quality in the room. This research was conducted with the aim of implementing an Internet of Things ( IoT )-based room temperature and humidity monitoring system using an ESP8266 microcontroller and a DHT22 sensor. The system was designed to be able to read temperature and humidity data in real-time, then send it to the ThingSpeak platform via the internet network. The research method includes hardware design, software development, and system performance testing in closed room conditions. Testing was carried out by collecting data at several observation times to see the stability of sensor readings and the data transmission process. The test results showed that the system could run well and stably, with an average temperature of 30.9 °C and an average humidity of 81.9%, and the data was successfully displayed in real-time on the ThingSpeak dashboard without significant data loss. Based on these results, the developed system can be used as a simple and applicable IoT -based room temperature and humidity monitoring solution.